2015
DOI: 10.1007/s11243-014-9906-x
|View full text |Cite
|
Sign up to set email alerts
|

Proton-coupled electron transfer reactions: kinetic studies on the oxidation of dihydroxybenzenes by heteropoly 10-tungstodivanadophosphate in aqueous acidic medium

Abstract: Kinetic studies on the oxidation of hydroquinone and catechol by the heteropoly 10-tungstodivanadophosphate anion, [PV V V V W 10 O 40 ] 5-, have been carried out in aqueous acidic medium at 25°C by UV-visible spectrophotometry. The oxidation of hydroquinone shows simple second-order kinetics overall, with first-order dependence of the rate on both [oxidant] and [hydroquinone] at constant [H ? ]. For catechol oxidation, the order of the reaction with respect to [oxidant] is unity, while the order with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 34 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…To date, there is only a single report describing the BDFE­(O–H) at the surface of a POM. Thermochemical analysis of the monoreduced, monoprotonated form of the heteropolytungsto­divanado­phosphate cluster, [PV 2 W 10 O 40 ] 5– , revealed a BDFE­(O–H) of 75.4 kcal/mol in acetonitrile . Notably, the authors describe selective formation of a bridging hydroxide ligand located between the two adjacent vanadium centers in the cluster as a result of the increased basicity of the reduced vanadium centers located within the assembly.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…To date, there is only a single report describing the BDFE­(O–H) at the surface of a POM. Thermochemical analysis of the monoreduced, monoprotonated form of the heteropolytungsto­divanado­phosphate cluster, [PV 2 W 10 O 40 ] 5– , revealed a BDFE­(O–H) of 75.4 kcal/mol in acetonitrile . Notably, the authors describe selective formation of a bridging hydroxide ligand located between the two adjacent vanadium centers in the cluster as a result of the increased basicity of the reduced vanadium centers located within the assembly.…”
Section: Resultsmentioning
confidence: 98%
“…While there have been a number of reports focused generally on the acid dependence of the electrochemistry of POMs, [26][27][28][29][30][31][32][33]45 to date there are few studies that investigate the thermochemistry of surface hydroxide moieties of the reduced variants of these metal oxide assemblies. 46 This is likely due to the fact that in addition to positive shifts in potential upon introduction of protons to the surface of the clusters, redox events tend to merge together and form multielectron/multiproton transfer events. [28][29][30][31][32][33]45 Indeed, the high-valent POV cluster reported here suffers a similar fate; acidification of an acetonitrile solution of V 6 O 13 results in the consolidation of single electron redox events (Figure S6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies in which PCET at POM surfaces has been explicitly investigated has revealed that the uptake of H-atom equivalents primarily occurs at bridging oxide positions. 12,18 An alternative mechanism for the generation of reactive Hatom equivalents at MO x surfaces invokes coordination-induced bond weakening of O-H moieties upon association of water to a surface oxygen-atom (O-atom) vacancy (Figure 1). In this scenario, a coordinatively unsaturated, reduced metal centre at the surface of the material binds to water, resulting in a weakening of the O-H bond of the substrate.…”
Section: Introductionmentioning
confidence: 99%